2020
DOI: 10.3390/cancers12061702
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Antagonist DWP05195 Induces ER Stress-Dependent Apoptosis through the ROS-p38-CHOP Pathway in Human Ovarian Cancer Cells

Abstract: In addition to their analgesic activity, transient receptor potential vanilloid 1 (TRPV1) agonists and antagonists demonstrate profound anti-cancer activities in various human cancers. In the present study, we investigated the anti-cancer activity of a novel TRPV1 antagonist, DWP05195, and evaluated its molecular mechanism in human ovarian cancer cells. DWP05195 demonstrated potent growth inhibitory effects in all five ovarian cancer cell lines examined. DWP05195 induced apoptosis through the activation of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…These results suggested that NAC blocked the effect of ROS on gastric cancer cells, indicating that ROS triggered cell death through DR5-mediated mitochondrial apoptosis pathway (31). ROS are the key molecules in the process of apoptosis (32,33). It is reported that moderate level of ROS can increase the ability of cell survival (34).…”
Section: Discussionmentioning
confidence: 88%
“…These results suggested that NAC blocked the effect of ROS on gastric cancer cells, indicating that ROS triggered cell death through DR5-mediated mitochondrial apoptosis pathway (31). ROS are the key molecules in the process of apoptosis (32,33). It is reported that moderate level of ROS can increase the ability of cell survival (34).…”
Section: Discussionmentioning
confidence: 88%
“…As for the mechanisms of ROS or ER stress induced JNK activation, many research articles reported that ROS induced ER stress, which has been popularly accepted 47‐49 . Previously, we tested the survival of pancreatic beta cell (MIN6 cells) in response to TG (ER stress inducer) or H 2 O 2 (a ROS molecule) and by comparison we found H 2 O 2 resulted in apoptosis in a shorter time duration compared with TG 4,5 .…”
Section: Discussionmentioning
confidence: 94%
“…In order to further confirm whether ERS is activated, CHOP was tested by western blot as a downstream gene of ERS. CHOP plays a role of convergent in ERS and controls the expression of stress‐induced genes related to apoptosis (Wang, Lee, et al, 2020). We also found that the expression level of CHOP increased in rat testis tissue.…”
Section: Discussionmentioning
confidence: 99%